PENERAPAN PEMBELAJARAN BERDIFERENSIASI DALAM MENGEMBANGKAN PERILAKU RELIGIUS PADA MATA PELAJARAN PPKN DI SMP NEGERI 1 TEMBUKU - Ayu Swandewi Trikusuma; I Ketut Sudarsana; Dewa Ayu Hendrawathy Putri (JAPAM (Jurnal Pendidikan Agama), 2025)
PPKN learning in schools is often focused on cognitive aspects only, such as memorization of concepts and theories, so it is less effective in shaping students' religious behavior motivations. It is a challenge for teachers to create learning that can tailor methods, materials, and levels of difficulty according to students' unique needs, so that it can help motivate students to behave religiously with a more contextual and individualized approach. Therefore, the application of differentiated learning in PPKN subjects is important to be analyzed. The data collected were then analyzed with Vigotsky's theory of Social Constructivism, Maslow's Hierarchy of Needs Theory, and Piaget's Theory of Cognitive Development. The results of this study show that the role of schools in supporting differentiated learning is to provide facilities and innovations to improve teachercompetence. Teachers as educators in schools play a role in providing stimulation and adaptive learning models in supporting differentiated PPKN learning. The maximum role of teachers and school managers is directly a manifestation of the school's role in supporting differentiated learning. The role of school interns in the success of differentiated learning in PPKN subjects shows success that can be seen through students' enthusiasm in participating in learning activities. Obstacles in the application of differentiated learning in PPKN subjects are more towards the aspect of opportunity and the strength of conventional learning ideologies of senior teachers. Meanwhile, factors that support the application of differentiated learning in PPKN subjects are the existence of adequate competence from teachers, as well as psychological approaches carried out by parents in the realm of informal education. The impact of differentiated learning on PPKN subjects at SMP Negeri 1 Tembuku is the development of students' religious behavior as shown by the emergence of internal motivation from students to be honest, empathetic, and independent in making decisions.